Advanced characterization of a stress corrosion crack from an in-field serviced X-52 steel line pipe - Jian Li; M. Elboujdaini; V. Y. Gertsman; David C. Katz (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
Analysis of stress corrosion cracking (SCC) usually involves high-end analytical tools including scanning electron microscope (SEM) and analytical transmission electron microscope (TEM). In recent years, focused ion beam microscope (FIB) has found many applications in materials science fields. In this study, high-resolution FIB images have shown details of crack morphology and a plan-view TEM specimen containing the selected crack-tip was successfully prepared. The preparation of cross-sectioned samples containing crack tips was of paramount importance for subsequent TEM analyses.